2020
DOI: 10.1016/j.ajg.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection among healthcare workers of a gastroenterological service in a tertiary care facility

Abstract: Background and study aims Frontlines healthcare workers (HCWs) during the coronavirus disease 2019 (COVID-19) pandemic are at increased risk of infection by SARS-CoV-2, but there are limited data on the prevalence of COVID-19 among HCWs in Egypt. This study aimed to assess SARS-CoV-2 infection among HCWs providing gastroenterological services. Subjects and methods Seventy-four HCWs at the gastroenterological service of Al-Manial University Hospital, the main hospital of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
3
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 22 publications
(19 reference statements)
5
37
3
3
Order By: Relevance
“…Mean age of HCWs ranged from 31.2 [ 51 ] years to 47.9 years [ 57 ], while sample size ranged from 25 [ 40 ] to 40,329 HCWs [ 14 ]. Regarding the study design, 26 studies were cross-sectional studies [ 14 , 15 , 18 , 19 , 21 , [23] , [24] , [25] , [27] , [28] , [29] , [30] , [31] , [32] , [34] , [35] , [36] , [37] , 39 , 44 , 47 , 52 , 54 , 58 , 60 , 61 ], 20 studies were prevalence studies [ 17 , 26 , 33 , 38 , [40] , [41] , [42] , [43] , 45 , 46 , [48] , [49] , [50] , [51] , 53 , 55 , 56 , 57 , 59 , 62 ], and three studies were cohort studies [ 16 , 20 , 22 ]. All studies except one [ 31 ] used a convenience sample, while response rate ranged from 47.7% [ 19 ] to 100% [ 36 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean age of HCWs ranged from 31.2 [ 51 ] years to 47.9 years [ 57 ], while sample size ranged from 25 [ 40 ] to 40,329 HCWs [ 14 ]. Regarding the study design, 26 studies were cross-sectional studies [ 14 , 15 , 18 , 19 , 21 , [23] , [24] , [25] , [27] , [28] , [29] , [30] , [31] , [32] , [34] , [35] , [36] , [37] , 39 , 44 , 47 , 52 , 54 , 58 , 60 , 61 ], 20 studies were prevalence studies [ 17 , 26 , 33 , 38 , [40] , [41] , [42] , [43] , 45 , 46 , [48] , [49] , [50] , [51] , 53 , 55 , 56 , 57 , 59 , 62 ], and three studies were cohort studies [ 16 , 20 , 22 ]. All studies except one [ 31 ] used a convenience sample, while response rate ranged from 47.7% [ 19 ] to 100% [ 36 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies except one [ 31 ] used a convenience sample, while response rate ranged from 47.7% [ 19 ] to 100% [ 36 , 60 ]. Forty-two studies were conducted in hospitals [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ], four studies in primary care facilities and hospitals [ 14 , 25 , 28 , 49 ], two studies in primary care facilities [ 35 , 62 ] and one study in cancer centers [ 59 ]. Thirty-five studies were published in journals [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , <...>…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 127,480 HCWs were included in this systematic review and meta-analysis. Forty-nine studies [14-62] reported data regarding the seroprevalence of SARS-CoV-2 antibodies among HCWs and 27 studies [14, 15, 18, 19, 21-25-27-32-34-37,39,44,47,52,54,58,60,61] investigated factors for SARS-CoV-2 antibodies positivity.…”
Section: Resultsmentioning
confidence: 99%
“…Mean age of HCWs ranged from 31.2 [51] years to 47.9 years [57], while sample size ranged from 25 [40] to 40,329 HCWs [14]. Regarding the study design, 26 studies were cross-sectional studies [14, 15, 18, 19, 21, 23-25,27-32,34-37,39,44,47,52,54,58,60,61], 20 studies were prevalence studies [17, 26, 33, 38, 40-43,45-46,48-51,53,55,56,57,59,62], and three studies were cohort studies [16, 20, 22]. All studies except one [31] used a convenience sample, while response rate ranged from 47.7% [19] to 100% [36, 60].…”
Section: Resultsmentioning
confidence: 99%